Analysis of the Implementation of a Learning Management System in Supporting the Digital Transformation of Education Based on Information Technology - dhiyaa riha aisya (COREAI: Jurnal Kecerdasan Buatan, Komputasi dan Teknologi Informasi, 2026)
This study aims to examine the use of Learning Management Systems (LMS) by highlighting their advantages, disadvantages, and implementation solutions in the context of online learning. LMS is a digital platform designed to facilitate distance learning processes, especially amidst the increasing demand for technology-based education. Literature analysis shows that LMS has several advantages, such as simplifying access to learning materials, providing flexibility in learning time, enhancing two-way communication, and providing systematic evaluation tools. However, its implementation still faces various shortcomings, including low interaction between teachers and students, minimal learning motivation, and suboptimal utilization of available features. To overcome these obstacles, solutions are needed in the form of ongoing training for educators, development of engaging content, and selection of LMS features that are appropriate to learning needs. The study's conclusion confirms that optimal use of LMS, by considering its advantages and addressing its disadvantages, can be an effective strategy for implementing quality online learning.